Brazilian adaptation and validation of the Empowerment of Parents in the Intensive Care‐Neonatology (EMPATHIC‐N) questionnaire - Dafne B.C.A. Gomez; Suely A. Vidal; Luciana C.S. Lima (Brazilian Society of Pediatrics, 2017)
Objectives: Considering the lack of questionnaires that propose to evaluate parental satisfaction with the Neonatal Intensive Care Unit (NICU) in Brazil, this study aimed to carry out the translation of the EMPATHIC‐N questionnaire into Brazilian Portuguese, the cross‐cultural adaptation and validation of its contents. Method: The translation and cultural adaptation of the questionnaire was carried out according to the protocol established by the Translation and Cross‐Cultural Adaptation Group of the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) in 2005. The validation of the content was carried out by a panel of experts, who evaluated each item from "very irrelevant" to "very relevant". Items with a mean Likert scale value <3.5 were excluded. Cronbach's alpha of the domains was calculated. Results: The questionnaire was submitted to two pilot tests with mothers of newborns admitted to the NICU of the study, after which some terms were modified to achieve global understanding. Cronbach's alpha remained above 0.7 in all items. Conclusion: The tool resulting from the translation, cultural adaptation, and validation of the EMPATHIC‐N questionnaire showed to be adequate to assess satisfaction of parents of newborns admitted to the NICU in Brazil.